Delving Into The University Students’ Perception of Instructors’ Code-Switching - Ousseini, Hassane (English Lecturers and Teachers Association (ELTA), 2024)
This study examined Abdou Moumouni University students’ attitudes towards Code-switching (CS) in an English language class. Data were collected from four English as a Foreign Language (EFL) learners through interviews and analyzed thematically. The results from the study revealed a couple of attitudes exhibited by participants. First, they thought that switching codes in an English class depends on the learners’ level. They believed that instructors do not need to use other languages than English in an EFL classroom, especially if the learners are at a higher level. Second, the research suggested that CS is necessary because it helps the learners to understand the teaching point. Finally, the study has identified learners’ lack of understanding of the lesson and limited vocabulary as the key factors that pushed the instructors to switch codes. Conducting a needs analysis is judged necessary to fully understand the reasons that motivate the students to register at the English department to develop adaptable and sensitive teaching materials. Keywords: Code-switching; Need analysis; Teaching Materials